2018
DOI: 10.1038/s41598-018-19465-0
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-13, a different prototype galectin, does not bind β-galacto-sides and forms dimers via intermolecular disulfide bridges between Cys-136 and Cys-138

Abstract: During pregnancy, placental protein-13 (galectin-13) is highly expressed in the placenta and fetal tissue, and less so in maternal serum that is related to pre-eclampsia. To understand galectin-13 function at the molecular level, we solved its crystal structure and discovered that its dimer is stabilized by two disulfide bridges between Cys136 and Cys138 and six hydrogen bonds involving Val135, Val137, and Gln139. Native PAGE and gel filtration demonstrate that this is not a crystallization artifact because di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 60 publications
7
48
0
Order By: Relevance
“…was also recently demonstrated for 1 other galectin family member, galectin-13, which exhibits approximately 54% amino acid identity with CLC/Gal-10. 68 Our results further show that CLC/Gal-10 interacts with the glycosylated human eosinophil granule cationic RNases, EDN (RNS2) and ECP (RNS3), but this interaction is not dependent on binding via N-or O-linked sugars, and it occurs even with bacterially expressed recombinant EDN devoid of any glycosylation. Of interest, CLC/Gal-10 also binds avidly to the large family of murine EARs, despite the lack of a CLC/Gal-10 ortholog in the mouse genome.…”
Section: Discussionsupporting
confidence: 60%
“…was also recently demonstrated for 1 other galectin family member, galectin-13, which exhibits approximately 54% amino acid identity with CLC/Gal-10. 68 Our results further show that CLC/Gal-10 interacts with the glycosylated human eosinophil granule cationic RNases, EDN (RNS2) and ECP (RNS3), but this interaction is not dependent on binding via N-or O-linked sugars, and it occurs even with bacterially expressed recombinant EDN devoid of any glycosylation. Of interest, CLC/Gal-10 also binds avidly to the large family of murine EARs, despite the lack of a CLC/Gal-10 ortholog in the mouse genome.…”
Section: Discussionsupporting
confidence: 60%
“…Investigations with galectin paralogues have shown that galectin-1 in the first term ovine gestation placenta prevented inflammatory processes that harm the fetus 55 , while galectin-13, which has the highest homology to CLC, is a member of the group of the so-called “pregnancy-related proteins”, due to its special immune functions at the feto-maternal interface 56 , 57 . These fundamental cell functions, already described for humans and other placental mammals, may indicate the path that connects our CLC findings and the selection pressure in the Andean hostile climate.…”
Section: Discussionmentioning
confidence: 99%
“…Although the structures of some prototype galectins (i.e. galectin-14, -16 and -17) have yet to be reported, most prototype galectin structures are known [ 34 , 53 , 54 , 55 , 56 ]. Crystallographic and biochemical analyses show that Gal-1, -2, -7 and -10 form dimers via non-covalent interactions [ 34 , 53 , 54 , 55 ].…”
Section: Structural Comparisons Between Gal-10 and Other Prototypementioning
confidence: 99%
“…Gal-13 is an unusual prototype galectin in that it forms dimers via disulfide bonds formed between two cysteine residues (Cys136 and Cys138) at the C-terminus of its CRD [ 56 ]. A variant with two mutations (C136S/C138S) exists as a monomer in solution [ 56 ].…”
Section: Structural Comparisons Between Gal-10 and Other Prototypementioning
confidence: 99%
See 1 more Smart Citation